Study of the method for assessing atmospheric turbulence by the envelope of sodar signals - Sheiko, S. (My University, 2018)
The method for measuring the intensity of atmospheric turbulence based on assessment of statistical characteristics of the sodar signal envelope was investigated. This method requires no changes to the sodar hardware, but rather gives the possibility to make fuller use of echo-signals in order to obtain meteorological information. Through theoretical analysis, it was shown that the echo-signal envelope is distributed by the Rice law. The parameter of the law of envelope distribution is unambiguously associated with intensity of atmospheric turbulence. Assuming standard stratification of the atmosphere, the values of the parameter of the law of envelope distribution for four classes of atmospheric turbulence according to the ICAO classification were calculated: weak, moderate, strong and storm. Convergence of the experimental law of distribution of the envelope of acoustic echo-signals to the theoretical law at different measurement time was studied. It was experimentally determined that the theoretical and experimental laws of distribution of the sodar signal envelope mismatch with probability of less than 5 % at measurement time from 10 to 30 minutes. The results of measurement using this method converge to a stationary value at measurement time of more than 10 min. The use of the examined method for assessment of atmospheric turbulence in addition to already used methods will make it possible to increase accuracy and time resolution of sodars. Досліджено метод оцінки атмосферної турбулентності за статистичними характеристиками обвідної сигналів содара. Показано, що обвідна ехо-сигналів розподілена по закону Райса, параметр закону розподілу пов'язаний з інтенсивністю турбулентності. Отримані значення параметра закону розподілу ехосигналів для турбулентності певних класів. Використання дослідженого методу додатково до вже застосованих дозволить збільшити точність і часове розрізнення содарів.
Keywords: acoustic sounding; aviation meteorology; sodar; turbulence; echo-signal; envelope; wind power industry; акустичне зондування; авіаційна метеорологія; содар; турбулентність; ехо-сигнал; обвідна; вітрова енергетика